Pembuatan Fruit Leather Kelopak Bunga Rosella (Hibiscus sabdariffa L.) dengan Penggunaan Pemanis Stevia dan Pektin - Hening Kenya Shafirani; Lilis Sulandari; Nugrahani Astuti; Ita Fatkhur Romadhoni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
A Research has been conducted on the production of roselle flower fruit leather using stevia as a natural sweetener substitute for sucrose and pectin as a stabilizing agent. This study involved variations in the amount of stevia sweetener (0.2 ml and 0.3 ml) and pectin concentrations (1% and 2% of the ingredient weight). Sensory evaluation of the fruit leather product included parameters such as color, aroma, taste, texture, and overall preference. The sensory test results showed that sample 620 was the best product, with a composition of 0.3 ml stevia sweetener and 2% pectin concentration. This product was characterized by a deep red color, a fresh sour aroma distinctive of roselle, a pliable texture that could be rolled, and a balanced sweet-sour taste that was preferred by the panelists. Nutritional content analysis of the best product, based on laboratory testing, revealed the following per 100g of fruit leather: 105.80 mg of antioxidants, 19.88 mg of vitamin C, 26.55% total sugar, 1.02% ash content, and 21.05% moisture content. Additionally, the selling price of the roselle flower fruit leather product was determined to be IDR 45,000 per 100-gram package.